2013
DOI: 10.1093/mnras/stt487
|View full text |Cite
|
Sign up to set email alerts
|

On the association of the ultraluminous X-ray sources in the Antennae galaxies with young stellar clusters★

Abstract: The nature of the ultra-luminous X-ray sources (ULXs) in the nearby galaxies is a matter of debates. One of the popular hypothesis associates them with accretion at a sub-Eddington rate on to intermediate mass black holes. Another possibility is a stellar-mass black hole in a high-mass X-ray binary accreting at super-Eddington rates. In this paper we find a highly significant association between brightest X-ray sources in the Antennae galaxies and stellar clusters. On the other hand, we show that most of the X… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 54 publications
8
59
0
Order By: Relevance
“…These results are in agreement with studies of the XLF of starforming galaxies (e.g., Grimm et al 2003;Mineo et al 2012) and of the location of ULXs in stellar clusters (e.g., Poutanen et al 2013), which conclude that ULXs are a high-luminosity end of the XRB population harboring most possibly stellarmass BHs rather than IMBHs.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in agreement with studies of the XLF of starforming galaxies (e.g., Grimm et al 2003;Mineo et al 2012) and of the location of ULXs in stellar clusters (e.g., Poutanen et al 2013), which conclude that ULXs are a high-luminosity end of the XRB population harboring most possibly stellarmass BHs rather than IMBHs.…”
Section: Discussionsupporting
confidence: 90%
“…Observations of the optical counterparts revealed that some of the ULXs are associated with young star clusters or star forming regions (Soria et al 2005;Kaaret 2005;Abolmasov et al 2007b;Grise et al 2008Grise et al , 2011Grise et al , 2012Avdan et al 2016a,b). These findings have been supported by identifying point like counterparts of ULXs with blue colors which indicative of early type, OB stars (Liu et al 2004;Grise et al 2005;Soria et al 2005;Roberts et al 2008;Poutanen et al 2013). These blue colors are consistent with emission from an irradiated accretion disk, however, it is noticed that the observed blue color may be partly due to contamination by the X-ray irradiation of the accretion disk and/or the companion star facing the X-ray source (Patruno & Zampieri 2010;Grise et al 2012;Jonker et al 2012;Vinokurov et al 2018).…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, they are good candidates to examine the population properties of ULXs. Poutanen et al (2013) had extensively examined the significant associations between ULXs and stellar clusters in Antennae galaxies. Using HST and VLT data supplemented with theoretical stellar isochrones, they estimated the ages of these clusters as < 6 Myr.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, they should stay within the clusters. It has been found [26] that all brightest X-ray sources in Antennae galaxies are located nearby to very young stellar clusters with an age less than 5 Myrs. It was concluded that the sources were ejected in the process of formation of stellar clusters in the dynamical few-body encounters.…”
Section: Pos(apcs2016)046mentioning
confidence: 99%